Effectiveness of dispersive solid phase extraction sorbents for sample clean-up by QuEChERs method for organochlorine pesticides determination in Pacific white shrimp - Omar, Norazlina (2013)
Organochlorine pesticides (OCPs) are persistent in the environments and have the ability to bioaccumulate in the food chain and are capable of causing various health hazards. The sample preparation techniques used for monitoring of OCPs in food are usually complicated, time consuming, use large volume of solvents and expensive. An ideal multi-residue method with high recoveries should be rapid, easy to perform, accurate, low cost and safer to the analyst due to less exposure to organic solvent and waste. The Quick Easy Cheap Effective Rugged and Safe (QuEChERS) is one of such methods. The objectives of this study are to evaluate the effectiveness of dispersive solid phase extraction (DSPE) sorbents in removing matrix interferences in Pacific white shrimp, to validate the most effective sorbent using the QuEChERS method and compare to the modified AOAC Official method 983.21. Thus, the QuEChERS sample preparation method DSPE and gas chromatography mass spectrometry (GC-MS) with selected ion monitoring mode (SIM) has been improved and applied for the analysis of common OCPs (α-HCH, β-HCH, γ-HCH, δ-HCH, trans-chlordane, cis-chlordane, p,p’-DDE, p,p’-DDD and p,p’-DDT) in Pacific white shrimp (Litopenaeus vannamei). The combination of primary and secondary amine (PSA), octadecyl (C18) and/or graphitized carbon black (GCB) have been evaluated as clean-up sorbents to samples collected from the state of Kedah, Selangor and Terengganu. Sampling was conducted twice a year between February - June and July - November 2011 at two selected farms from each state. The results have shown the mean recoveries for PSA:C18, PSA:GCB and PSA:C18:GCB ranged between 93–100%, 98-105% and 98-105%, respectively. The relative standard deviations (RSD) of <14%, <15% and <10% were obtained for PSA:C18, PSA:GCB and PSA:C18: GCB, respectively. The PSA:C18 was not able to remove matrix interference, such as cholesterol. The sorbent efficiency to minimize matrix interferences was PSA:C18:GCB > PSA:GCB > PSA:C18. In the validation study, PSA:C18:GCB was validated for selectivity, limit of detection (LOD), limit of quantification (LOQ), linearity and working range, matrix effect, recovery, trueness and precision using the QuEChERS method. The range for LOD and LOQ were 0.9 - 4.5 ng/g and 3 - 15 ng/g, respectively. The correlation coefficients for matrix-matched calibration curves >0.99 were obtained. All analytes had matrix enhancement effects with mild effect for -HCH, medium for -HCH, -HCH, -HCH, trans-chlordane, cis-chlordane and strong effect for p,p’-DDE, p,p’-DDD and p,p’-DDT. Mean recoveries of 98 – 105% with associated RSD of <4.2% had been obtained for the QuEChERS method. By using the modified AOAC Official Method 983.21, LOD and LOQ values for all OCPs were between 15 – 30 ng/g and 50 – 100 ng/g, respectively. The correlation coefficients for matrix-matched calibration curves >0.96 were obtained for the modified AOAC Official Method 983.21. All OCPs had mild signal suppression effects for the modified AOAC Official Method 983.21. Mean recoveries of 76 – 110% with associated RSD <6% were obtained. In term of LOD, LOQ, linearity, trueness and precision, the results indicated that the QuEChERS method was better than the modified AOAC Official Method 983.21. The validated QuEChERS method had been applied for the determination of nine OCPs in 65 samples from selected farms in Malaysia. OCPs were not detected in all samples. The results have indicated that this method could be adopted in routine analysis to reduce inspection time and cost of analysis and be used towards the International Standard requirements for laboratory accreditation.